Analyzing the Impact of PT AMMAN's Community Development and Empowerment Program on Brand Image - Agsah, Nabila; Roostika, Raden Roro Ratna (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
The Community Development and Empowerment Program is a government initiative aimed at enhancing the human development index and fostering economic growth within communities neighboring the mine, encompassing post-mining implementation. This program is intricately linked to the company's reputation, observable through the effective execution of activities to attain the program's objectives. PT AMMAN, a mining enterprise, has actively engaged in implementing such a program. This study endeavors to evaluate the impact of PT AMMAN's Community Development and Empowerment Program on its corporate image. Employing a questionnaire, this research was conducted among beneficiaries in West Sumbawa Regency. The collected data underwent validation, reliability, and normality tests using SPSS software. Factor analysis was then performed to identify the elements influencing PT AMMAN's corporate image. The results indicate that the Community Development and Empowerment Program significantly contributes to the company's image, particularly in the economic sector. Key aspects include MSME training and mentorship programs, business and financial management training, and infrastructure development. Notably, the Community Development and Empowerment Program garnered highly positive impressions from beneficiaries, with an exceptional rating of 86.93%.